2005
DOI: 10.1080/10473289.2005.10464606
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Sources of Atmospheric Aerosol at a Hot Spot Area in Dhaka, Bangladesh

Abstract: Samples of fine and coarse fractions of airborne particulate matter were collected at the Farm Gate area in Dhaka from July 2001 to March 2002. Dhaka is a hot spot area with very high pollutant concentrations because of the proximity of major roadways. The samples were collected using a "Gent" stacked filter unit in two fractions of 0-to 2.2-m and 2.2-to 10-m sizes. The samples were analyzed for elemental concentrations by particle-induced X-ray excitation (PIXE) and for black carbon by reflectivity methods, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 33 publications
1
52
0
Order By: Relevance
“…Gate is a also hot spot site due to the proximity of several major roadways intersection and large numbers of vehicles plying through the area (Begum et al 2005). The site is in the mixed area (i.e., commercial and semi-industrial area).…”
Section: Methodsmentioning
confidence: 99%
“…Gate is a also hot spot site due to the proximity of several major roadways intersection and large numbers of vehicles plying through the area (Begum et al 2005). The site is in the mixed area (i.e., commercial and semi-industrial area).…”
Section: Methodsmentioning
confidence: 99%
“…Data from this site has been previously examined for source apportionment. 2 Motor vehicles were estimated to contribute ϳ50% of the PM 2.2 at this location. The purpose of the present study was to assess the effect of the removal of two-stroke baby taxies on air pollution based on PM and black carbon (BC) data obtained from this site.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The other sources of PM emissions are brick kiln around Dhaka, which mainly operate during the winter period, resuspension from all of the dusty unpaved roads, and refuse burning by slum dwellers. From source apportionment studies, 2 it was found that ϳ50% of PM Ͻ2.2 m (PM 2.2 ) comes from vehicular emissions. Thus, vehicles are believed to constitute the dominant source of air pollution in Dhaka.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been studies of the particulate matter concentrations and compositions for over a decade (Salam et al, 2003: Biswas et al, 2003Begum et al, 2004Begum et al, , 2005Begum et al, , 2010Begum et al, , 2013 (Begum et al, 2013). Many of these studies have included receptor modeling to identify the major source types contributing to the observed PM.…”
Section: Introductionmentioning
confidence: 99%